Predicting the demand for preschool teachers in China under the three-child policy: a comparative analysis between Guangdong Province and Jilin Province - Xu, Dongyuan; Wang, Zhichao; Zhang, Jiwei (Frontiers in Psychology, 2025)
IntroductionThis study predicts the development trends of the scale of preschool children in kindergartens and the demand for full-time teachers in Guangdong Province and Jilin Province under the context of three-child policy, while exploring inter-provincial differences and their underlying reasons.MethodsBased on the statistical data released by the national and provincial regions, we constructed and trained two Long Short-Term Memory (LSTM) neural network models for prediction.ResultsFrom 2023-2035, the scale of preschool children in kindergartens and the demand for full-time teachers in Guangdong Province exhibit an overall upward trend, while in Jilin Province, both exhibit an overall downward trend. The opposite development directions of the two provinces are the result of the combined effects of factors such as the level of economic development, population structure, and culture.DiscussionOur findings provide data support for local governments to formulate education policies that are coordinated with the changes in the school-age population and the demand for teachers. It also has reference significance for foreign countries.